2022
DOI: 10.1093/femsyr/foac035
|View full text |Cite
|
Sign up to set email alerts
|

Yeast osmoregulation – glycerol still in pole position

Abstract: In response to osmotic dehydration cells sense, signal, alter gene expression and metabolically counterbalance osmotic differences. The main compatible solute/osmolyte that accumulates in yeast cells is glycerol, which is produced from the glycolytic intermediate dihydroxyacetone phosphate. This review covers recent advancements in understanding mechanisms involved in sensing, signaling, cell-cycle delays, transcriptional responses as well as post-translational modifications on key proteins in osmoregulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 131 publications
(200 reference statements)
0
34
0
Order By: Relevance
“…In particular, the determinant role of mitochondria in osmotic stress has been highlighted, although the molecular details are far from being elucidated [ 14 , 15 , 16 ]. Recently, we reported that the RTG pathway acts downstream of HOG1 , the master regulator of osmostress response, and sustains mitochondrial respiratory capacity upon salt stress [ 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the determinant role of mitochondria in osmotic stress has been highlighted, although the molecular details are far from being elucidated [ 14 , 15 , 16 ]. Recently, we reported that the RTG pathway acts downstream of HOG1 , the master regulator of osmostress response, and sustains mitochondrial respiratory capacity upon salt stress [ 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under hyperosmotic conditions, yeast cells synthesize or retain high concentrations of glycerol to maintain their osmotic balance (Blomberg, 2022, de Nadal & Posas, 2022, Hohmann, 2002). Intracellular glycerol concentration is partially regulated by Fps1, an aquaglyceroporin on the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…There are roughly 570 genes that respond to increased osmolarity in a Hog1-dependent manner, however, only a subset of those (32 genes) appears to be fully Hog1-dependent [ 29 , 30 ]. Examining the published expression changes upon caffeine addition [ 5 ] ( https://www.ncbi.nlm.nih.gov/sites/GDSbrowser?acc=GDS2914 ) we found that fully Hog1-dependent genes like STL1, TKL2, GRE2, DAK1 and PGM2 do not respond to caffeine.…”
Section: Discussionmentioning
confidence: 99%